PERBEDAAN RERATA KADAR ENDOTELIIV-I PADA PDREMPUAN DENGAI DIABETES MELITUS TIPE 2 OBES DAN NON OBES - , dr. Yanti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background. Type 2 diabetes is the most common type of diabetes. About 85% are people with type 2 diabetes and 90% of those with obesity or overweight. Several previous studies showed elevated levels of endothelin-1 (ET-1) in patients with type 2 diabetes are obese compared to non-obese. Epidemiologically, central obesity associated with type 2 diabetes through insulin resistance. Insulin resistance is a state of hyperinsulinemia with decreased ability of peripheral insulin action in muscle and liver especially. In a state of insulin resistance are increased levels of ET-1. Aim. To evaluate the difference plasma levels of endothelin-1 in women with type 2 diabetes mellitus obese and non-obese. Methods. Cross-sectional design was conducted on women with type 2 diabetes from clinic of the Endocrine and Metabolic RSUP. Sardjito Yogyakarta . ELISA sandwich,s method was used to measure plasma levels of endothelin-. 1. Characteristics of the study subjects are presented in the form of mean and standard deviations. The difference in the mean levels of endothelin-1 between the DM type II obese and non obese analyzed by independent T test, when normal distribution and the Mann Whitney U test if the distribution is not normal. Statistical analysis using SPSS 17 with the value of P is considered significant if the p-value <0.05 with 95% confidence intervals. Results. Result will be presented as dummy table.